Studi tentang Modified Pecking Order di Bursa Efek Indonesia - Arni Surwanti (Jurnal Manajemen Bisnis, 2011)
this study examines whether there is market reaction to the presence of external financing decisions on companies in the Indonesia Stock Exchange under the Modified Theory pecking order